KOMUNIKASI KELOMPOK UNIT KEGIATAN MAHASISWA BAHASA DAN SASTRA UNIVERSITAS RIAU (UKM BATRA UR) DALAM MENGEMBANGKAN KREATIVITAS TEATER ANGGOTA - Manurung, Yuni Sri Ningsih; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
University is one of the places where many organizations/communities are found, including at the University of Riau, one of which is Ukm Batra from the only arts field at Riau University who channels artistic talents, such as in the fields of theater, music and literature, UKM BATRA has recognized by artists in Riau Province, so that many participants and administrators are recommendations from artists and also Batra alumni of course. This study aims to determine the behavior of group members, how the member's theater creativity is and what are the factors that affect the effectiveness of group communication in developing members' theater creativity. This study used qualitative research methods, with data collection techniques, observation, interviews, and documentation. The selection of informants used a purposive technique, selecting five selected informants, namely a chairman of UKM BATRA, one coach, two administrators and two active members of UKM BATRA Pekanbaru. For data analysis techniques, refer to Miles and Huberman's interactive model. Checking the validity of the data used the participation extension technique and triangulation. The results of this research show that UKM BATRA has a behavior that is closely related to collaborations that can be carried out by anyone as well as actively participating in activities, each member adapts himself by restraining his own ego, blending is done by putting mutual interests first. The form of group communication that occurs in this group is found in the form of descriptive group communication, through three approaches, task groups, group meetings and awareness groups. Of the three things, it is found that activities are carried out in developing members' theater creativity, namely, maintaining cohesiveness, training, participating in theater performances and see / read literature. Effectiveness is seen from two sub-focuses, namely situational factors using democratic leadership, the existence of shared interests and hobbies and the communication network formed is an all-channel scheme. Personal factors, the openness of group members and roles in the group according to their function, the act of communicating is carried out directly and is allowed to anyone at any time. Keywords: Group Communication, UKM BATRA UR, Creativity, Theater